METHODOLOGICAL JUSTIFICATION OF MANAGEMENT DECISIONS IN THE INVESTMENT AND INNOVATION SPHERE - IZHEVSKYI, Pavlo; HNATYK, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the study, attention is updated to the issues of management of the processes of investment and innovation development of business entities. The purpose of the research is to form methodological and applied support for the justification of management decisions in the field of investment and innovation development of economic entities.It is shown that the restoration and further strengthening of competitive positions, increasing the social and economic efficiency of enterprise management requires a more active and systematic introduction of innovations. It was concluded that one of the most important prerequisites for innovative activity is its financial, in particular, investment support. It is shown that the substantiation of the theoretical-methodical and applied basis for the justification and adoption of management decisions in the field of investing in the innovative development of enterprises is becoming highly relevant. It is pointed out that there is still a lack of a full-fledged methodology for justifying management decisions in the field of investment and innovation development of enterprises.It has been established that the application of the investment-innovation approach to the development of enterprises, which means a specific type of strategic management decision-making in the field of operation and development, which allows directing business processes to new, more effective parameters, covering all aspects of the enterprise's activities and ensuring their improvement in innovative ways principles, today it is becoming more and more irreplaceable.It is substantiated that in order to ensure a sufficient variability of innovative approaches to development, the classification of their types should be applied, supplemented by approaches based on such classification features as competitive positions on the innovation market, the target orientation of financing of innovative activity, its directions, types of innovation policy, functional areas of innovation implementation.The applied value of the research results lies in the formation of a qualitative system of substantiation of management decisions at domestic enterprises through the implementation of an investment-innovation mechanism for supporting investment-innovation activities, which consists of a set of methods and tools for investment support for innovative development based on the use of internal and external financial and investment assets, institutional basis, organizational and information support.The scientific novelty of the research results lies in the identification of methods (forecasting and planning, budgeting, analysis, scenario modeling, regulatory and balance analysis, controlling, auditing, monitoring and technology outsourcing) and tools (normative regulation, economic incentives, standardization, reporting, informing, automated management and programming) investment support for innovative development of business entities.
Keywords: investment and innovation activity; development; efficiency; activation; justification of management decisions; methodical approaches